Expert Panel Recommendations on the Clinical Practice Guidelines for the Diagnosis and Management of Invasive Candidiasis in Indonesia - Anna Rozaliyani; Erni Juwita Nelwan; Mardiastuti Wahid; Dita Aditianingsih; Mulya Rahma Karyanti; Siti Pratiekauri; Adityo Susilo; Fathiyah Isbaniah; Heidy Agustin; Yulia Rosa Saharman; Robiatul Adawiyah; Findra Setianingrum; et al. (Interna Publishing, 2024)
Invasive candidiasis (IC) ranks among the primary causes of deadly fungal infections. The frequency of IC rises alongside increasing number of patients with altered immune systems, critically ill, chronic diseases, and various medical procedures. The disease causes high morbidity and mortality, as well as prolonged stay and increases hospital costs. The diagnosis and management of IC in Indonesia is still a challenge. Laboratory facilities in identifying pathogenic fungi and susceptibility tests to antifungals are still limited. Clinical awareness and financial support from health policymakers are also insufficient. Early diagnosis is essential for proper treatment to reduce morbidity and mortality rates. Initiated by the Indonesian Pulmonary Mycoses Centre (IPMC), several expert representatives from six medical professional organizations in Indonesia have agreed to set up a meeting series to prepare a joint draft on the diagnosis and management of IC. The expert panel aimed to achieve a consensus on the clinical practice guidelines for diagnosing and treating IC in Indonesia.